Dinamika Kerjasama Keamanan Siber antar Negara : Studi Kasus Indonesia Dan Belanda - Muhammad Faiq Qushayyi (Journal of Peace, Security and Democracy, 2025)
The rapid development of information technology in the era of globalization has brought new challenges in the field of cybersecurity. As a country with a high internet adoption rate, Indonesia faces various cyber threats that can damage critical infrastructure and threaten socio-political stability. In the face of these challenges, international cooperation is becoming increasingly important, and one significant form of cooperation is between Indonesia and the Netherlands. This article examines the impact of cybersecurity cooperation between the two countries in improving Indonesia's capacity to deal with cyber threats. Through a qualitative approach, it explores the various initiatives that have been implemented, including training programs, information exchange, and joint policy development to improve Indonesia's cyber resilience. It found that this cooperation not only strengthens the technical aspects but also facilitates the formation of more holistic policies in addressing cyber challenges. The article also discusses the obstacles faced in this collaboration, including differences in infrastructure, human resource capacity, and political and legal aspects that may affect the effectiveness of this collaboration. Finally, the article offers strategic recommendations for both countries to strengthen their cooperation, with a focus on strengthening Indonesia's national capacity and integrating cybersecurity policies at the international level.